The Increasing of Competitiveness of Agro-Industry Products Through Institutional Empowerment to Support the Achievement of Sustainable Agricultural Development - Faqih, Achmad; Elizabeth, Roosganda; Azahari, Delima Hasri (International Journal of Energy Economics and Policy, 2020)
The aim of present literature is to examine the importance of institutional empowerment comprehensively related to the increasing competitiveness of agro-industry products in the perspective of bio-industrial agriculture for the achievement of sustainable agricultural development, which is enriched with a review of various studies and other related literature by using a quantitative descriptive method. The depletion of petroleum reserves and the length of the process of the formation of fossil fuel materials require us to immediately innovate to produce alternative and renewable energy, and some of them have been produced from various bio-industrial studies. The use of bioenergy in agro-industry is predicted to be able to make efficient and effective the use of fuel oil and GMP of its processed products. The findings also exposed that positive links among the renewable energy resources, management of natural resources, management of human resources and sustainability of agriculture development. These findings are provided with the guidelines to the policymakers that they should increase their emphases on the renewable energy that enhance the growth of the economy. Keywords: Bio-Refinery, Empowerment, Renewable Alternative Energy, Food Prosperity JEL Classifications: Q16, L66, Q24 DOI: https://doi.org/10.32479/ijeep.10376